2007
DOI: 10.1111/j.1467-8683.2007.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Development of the Internal and External Service Tasks of Non‐executive Directors: the case of the Netherlands (1997–2005)

Abstract: During the last decade, globalization and liberalization of financial markets, changing societal expectations and corporate governance scandals have increased the attention for the fiduciary duties of non-executive directors. In this context, recent corporate governance reform initiatives have emphasized the control task and independence of non-executive directors. However, little attention has been paid to their impact on the external and internal service tasks of nonexecutive directors. Therefore, this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 55 publications
2
21
0
2
Order By: Relevance
“…Model 3a, Model 3b and 3c model also showed an increase of respectively 3.2% and 3.9% of the company's performance. These findings are consistent with evidence from Bezemer et al (2007Bezemer et al ( , 2012 in their study in the Netherlands with the finding that the two boards gave wider opportunities to the majority shareholders to play a role in overseeing the operations of the firm through a separate board up can have an impact on firm performance. Another reason that may be attributed to the above findings is the average equity holdings by individuals and families who are at a high level, which is 49.53% and is seen more concentrated compared to the situation in countries that have a system of a board (Kamal, 2010).…”
Section: The Effects Of Family Ownership On Firm Performancesupporting
confidence: 81%
See 1 more Smart Citation
“…Model 3a, Model 3b and 3c model also showed an increase of respectively 3.2% and 3.9% of the company's performance. These findings are consistent with evidence from Bezemer et al (2007Bezemer et al ( , 2012 in their study in the Netherlands with the finding that the two boards gave wider opportunities to the majority shareholders to play a role in overseeing the operations of the firm through a separate board up can have an impact on firm performance. Another reason that may be attributed to the above findings is the average equity holdings by individuals and families who are at a high level, which is 49.53% and is seen more concentrated compared to the situation in countries that have a system of a board (Kamal, 2010).…”
Section: The Effects Of Family Ownership On Firm Performancesupporting
confidence: 81%
“…In the short term, this behavior will maintain the performance, while the performance of the firm can be done gradually in the long run. Consistent with this point, Bezemer et al (2007Bezemer et al ( , 2012 found in his study that the BOC members involved in controlling BOD managers can improve compliance and reduce the risk of failure but reduced in other firms focusing on innovation and research and development firms (Hendry & Kiel, 2004;Sundaramurthy & Lewis, 2003). On the other hand, family involvement in the two boards reduces conflicts of interest between the BOC and BOD and provides a positive influence on firm performance.…”
Section: The Effect Of Family Involvement In Both Boards (Boc and Bodsupporting
confidence: 51%
“…Corporate interlocking is a means of anticipating or controlling sources of uncertainty stemming from potentially disruptive unilateral actions of other corporations (Allen, 1974). Bezemer, Maassen, Van Den Bosch and Volberda (2007) explain that board interlocking can provide benefits to companies connected in a network, improving performance of organizations connected by sharing their directors. However, the relationships of the Board of Directors can compromise the independence of non-executive directors, generating conflicts of interest.…”
Section: Board Interlocking and Performance Of The Companiesmentioning
confidence: 99%
“…For more detailed descriptions of the Dutch corporate governance context, see Bezemer, Maassen, van den Bosch, and Volberda (), De Jong et al (), De Jong, Roell, and Westerhuis (), Groot (), Kabir et al (), and Van Ees et al ().…”
mentioning
confidence: 99%